Synthetic Studies on Lolium Alkaloids - Zuschlag, Daniel; Cakmak, Mesut; Kuttruff, Christian A.; Mayer, Peter; Trauner, Dirk (Synthesis, 2025)
We report the first total synthesis of several natural products of the loline family, including the unusual chloropyrrolizidine alkaloid lolidine. We demonstrate the utility of an azide intermediate in our synthesis toward click-chemistry and late-stage functionalization. Lastly, we further explore the CO2 absorbing properties of temuline, as well as a potential application of loline as a chiral ligand in palladium chemistry.
Keywords: Lolidine; Loline; Temuline; Alkaloid; Total synthesis; Click-chemistry; CO2 absorption